Economic Groups and the Mining Bonanza in Peru - Torres Cuzcano, Víctor (2014)
This paper analyzes the organizational strategies of the five most important national economic groups in the Peruvian mining industry – Buenaventura, Brescia, Volcan, Hochschild, and Milpo – during the first decade of this century, a period characterized by a sustained mining boom resulting from rising international prices of metals and by increased socio-environmental conflicts. In the unprecedented context of the boom, these mining groups strengthened their finances as a result of windfall profits, reformulated their business strategies in response to socio-environmental conflicts, reinforced (with the exception of Milpo Group) their principal characteristic as enterprises under the control and ownership of Peruvian families, and initiated the internationalization of their investments.